The Meaning of the Functions and Motives of the Toba Batak Ethnic Ragidup Ulos: A Semiotic Study - Noni Monalisa Manik; Ramlan Damanik (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article is entitled The Meaning of the Functions and Motives of the Toba Batak Ethnic Ragidup Ulos: A Semiotic Study. Ragidup Ulos has a symbol of life. said Ulos Ragidup because the colors, paintings and patterns (yeast) give the impression that ulos is really alive. This study aims to describe the motifs found in the Batak Toba ethnic Ragidup Ulos, to describe the functions and meanings of the symbols found on Ragidup Ulos. The theory used to analyze the data from this research is a semiotic theory, namely symbols put forward by Charles Sanders Peirce. The method used in this research is qualitative method. Based on the results of the research, in Ragidup Ulos there are 14 motifs which include: Jogia, Batu Assimun, Sigumang, Pamaltahi, Pinarhalak Boru, Pinarhalak Bawa, Centipede-Centipede, Ipon-Ipon, Rungkung Anduhur, Honda-Honda, Flowers, Simakkat- Akkat, Hotang-Hotang and Rambu. In addition to the types of motifs, in the Ragdup ulos also discussed the function and meaning of the Ragdup ulos motif.